(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Nanotechnology is the study of nanoparticle and their novel properties of material. From the current scenario of construction industry it has been seen that there are many drawbacks in terms of various properties such as cracks, shrinkages ,bulking of sand, expansion in joints ,punching of soil, differential settlement in soil, etc. which occur in structure using traditional materials. It may be sometimes emits carbon dioxide which cause pollution. Therefore this structure have less service life and high life-cycle cost. Nanocomposite material can generate products with many unique characteristic that can improve current construction materials like lighter stronger structural composites, better cementations materials, lower thermal transfer rate of fire retardant insulation. These review paper going to highlight summarise different phenomenon of nanocomposites material and their methodological effect along with specific applications.